Settlement of Inheritance Disputes by A Mediator Through Mediation at The Bima Religious Court - Andi Muhammad Galib; Zuhrah Zuhrah; Muhammad Amin (Jurnal Ilmiah Teunuleh, 2026)
This study examines the mediation of inheritance disputes by mediators at the Bima Religious Court. Inheritance disputes often lead to ongoing debates due to differences in interests, understanding of Islamic inheritance law, and the influence of customs and family relationships. Therefore, mediation is considered a solution that can foster harmony and maintain relationships between heirs. This study aims to analyze how mediation is conducted, the factors that contribute to its success, and the factors that cause its failure in resolving inheritance disputes at the Bima Religious Court. This study uses empirical methods. Data were collected through interviews, observations, and documentation involving judge mediators, non-judge mediators, and other related individuals. The results show that the mediation process occurs in several stages: pre-mediation steps, mediation, and implementation of mediation results in accordance with PERMA Number 1 of 2016. The success of mediation is influenced by the mediator's neutrality, ability to facilitate communication, and the sincere intentions of the participants. However, mediation may be unsuccessful due to a lack of participants or the mediator's lack of understanding of the issues at hand. Therefore, increasing the effectiveness of mediation requires strengthening the role of the mediator and increasing the parties' recognition of the value of achieving a peaceful resolution.